Pengaruh Perbandingan Sosial dan Materialisme terhadap Pembelian Impulsif Melalui Pengendalian Diri Sebagai Pemoderasi - Mardiyah, Arrifah Ainul (Universitas Syiah Kuala, 2025)
This study aims to examine the influence of social comparison and materialism on impulsive buyingbehaviorand to evaluate the role of self-control as a moderating variable among Generation Z Shopee e-commerce users in Sleman Regency, Yogyakarta Special Region. The background of this study stems from the phenomenon of high unplanned online shopping activity among Generation Z due to social pressures and growing materialistic values in the digital era. This study used a quantitative approach with a survey method and distributed questionnaires to 94 respondents selected using a purposive sampling technique. Data analysis was conducted using theSmartPLSapplication version 3.2.9. The results showed that social comparison and materialism had a positive and significant effect on impulsive buying. However, self-control was shown to weaken the influence of materialism on impulsive buying but did not significantly moderate the relationship between social comparison and impulsive buying. This study provides theoretical contributions to understanding the psychological and social dynamics that drive digital consumerbehaviorand offers practical implications for developing more responsible marketing strategies for young consumers.